Chinese labour in the global economy: an introduction - Bieler, Andreas; Lee, Chun-Yi (Taylor and Francis, 2016)
This Introduction outlines the main purpose of this special issue volume: to analyse new forms of resistance by Chinese workers against conditions of super-exploitation. After an assessment of the new international division of labour, we provide an overview of Chinese production in the global economy, followed by an introduction of the contributions to this volume.